„Моя двойная жизнь” Сары Бернар в восприятии М. Цветаевой - Войтехович, Роман (Studia Rossica Posnaniensia, 2017)
The article is devoted to Marina Tsvetaeva’s perception of Ma Double Vie (1907) by Sarah Bernhardt. The poem Sara v Versal’skom monastyre is analyzed, as well as other works by Tsvetaeva. The book by Bernhardt is one of the pillars of Tsvetaeva’s autobiographical myth, including the image of the coffin in which Sarah was having a rest and anecdotes about this coffin. Even the appearance of the poet (her haircut) reflects one of Bernhardt’s scenic images.